2017
DOI: 10.1111/cdoe.12345
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ opinions on using digital technologies in dental practice

Abstract: Opinions on digital technologies among dentists and motivating work aspects vary with level of technology use. Being more focused on technologies and perceiving a higher added value from using them are associated with using more digital dental technologies, when taking into account motivating work aspects and characteristics of the dentist and dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
0
20
1
6
Order By: Relevance
“…Furthermore, Joda & Brägger [16] demonstrated that the digital implant-prosthetic workflow costs 18% less as compared to the conventional approach. Despite that, dentists seem to believe that the digital workflow is not costeffective [17]. The laboratorial and clinical costs involved are commonly reduced in the digital workflow, which leads to a potential increase in the dentist's productivity and profit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Joda & Brägger [16] demonstrated that the digital implant-prosthetic workflow costs 18% less as compared to the conventional approach. Despite that, dentists seem to believe that the digital workflow is not costeffective [17]. The laboratorial and clinical costs involved are commonly reduced in the digital workflow, which leads to a potential increase in the dentist's productivity and profit.…”
Section: Discussionmentioning
confidence: 99%
“…While the digital workflow remains an important advance in dentistry, enabling a more efficient and streamlined treatment, it is not routinely accessible to clinicians. We did not experience an easy access to the tools and components used in the CAI/CAD/CAM protocol, although the literature shows a tendency to greater diffusion of the digital workflow among clinicians in the near future [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En recientes estudios se menciona que en el Reino Unido el 56% de los odontólogos no usa o no está interesado en implementar algún tipo de tecnología CAD/CAM en su práctica, y en Suiza, sólo el 23% de los clínicos utilizan esta tecnología en sus consultas 30 . Si bien estos números pueden considerarse desalentadores, una de las premisas importantes de este estudio fue que se observó que, a menor edad del odontólogo, existía una mayor posibilidad de implementación tecnológica en su práctica clínica 30,31 , lo cual contrasta con el grado de integración digital en las mallas curriculares de pregrado, las que en su mayoría carecen de educación digital 32 . Hoy en día la tecnologización de la clínica se relaciona más a una motivación personal que a una necesidad real, y es en este ímpetu en el que recae la creación de técnicas híbridas o digitalmente indirectas que permiten adentrarse de manera paulatina en este flujo de trabajo.…”
Section: Implementación Del Flujo Digital En La Clínicaunclassified
“…Intraoral cameras (IOC) are used by dentists to show a patient their interior surface of their mouth, as an alternative to mouth mirrors (Sharma et al, 2019;van der Zande et al, 2018). It was irst invented in the year 1989.…”
Section: Intraoral Cameramentioning
confidence: 99%